Diagnosis and decision making for current oxidative and reductive bleaching treatments used on paper - Sigourney Smuts (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Bleaching of paper artefacts has recently become a highly contentious issue with scientific research indicating risks to both media and support. However, there remain occasions where bleaching enhances legibility or improves aesthetic appreciation. A thorough review of the literature is presented to offer practical advice and a better understanding of the chemistry behind the processes, thus minimising risks.